Plate Wiper: A Novel Plate Washing Machine using Dry Sand and Wiper to Save Water - Arathi Nashi , Husnara Pinjar, Deepti Challagidad, Savita Girijavvagol, Krishnamurthy Bhat (International Journal of Advanced Science and Technology, 2020)
— Dish and plate wash is an art and it is an integral part of everyday life. Dishes and plates were cleaned manually for a long time by humans. As the technology advances, man-made semi and fully automated machines are invented to ease and enhance the life style. Be it manual or automated machine wash, the process of cleaning requires large amount of water. In order to save precious water, scientific community needs to invent machines which require less or no water for the said purpose. In this paper, a novel method of dish plate cleaning machine which uses sand instead of water is proposed. It is a microcontroller based fully automatic machine and the cleaning extent is expected to be highly acceptable. Plate washer is an electrically operated machine which washes the dishes cleanly in less time with minimum or no water and can be reused immediately. The proposed machine can save lots of water. In the wake of saving precious water and highly affordable cost, it has potential market value also. Two variants to be thought of: One for the general kitchen use and other for mass/large scale cleaning. The implementation of this machine is already initiated and it will be a boon to the individual and mass customers. The machine proposed in this paper is “Plate wiper” instead of “Plate washer”.’